Medieval women religious, c. 800-c. 1500 : new perspectives - Curran, Kimm; Burton, Janet (Medievalist) (Studies in the history of medieval religion, 2023)
"Medieval women found diverse ways of expressing their religious aspirations: within the cloister as members of monastic and religious orders, within the world as vowesses, or between the two as anchorites. Via a range of disciplinary approaches, from history, archaeology, literature, and the visual arts, the essays in this volume challenge received scholarly narratives and re-examine the roles of women religious: their authority and agency within their own communities and the wider world; their learning and literacy; place in the landscape; and visual culture. Overall, they highlight the impact of women on the world around them, the significance of their presence in communities, and the experiences and legacies they left behind"--